Automated Greenhouse Self-controlled Farming Fields - Fahad Almansour (Communications of International Proceedings, 2021)
Smart agriculture is a management concept aimed at providing the agriculture industry with the infrastructure to take advantage of cutting-edge technologies - including big data, the cloud and the Internet of Things (IoT). In this paper, we propose a smart solution based on the Internet of Things, which consists of setting up a monitoring and control system to automatically manage watering, humidity, temperature, humidity and the brightness in a greenhouse. In addition, the farmer will be able to collect and analyze in real time the bioclimatic indicators. Such a system is able to identify and verify people and give them or not access according to the permissions granted beforehand.
Keywords: IoT; WSN; Smart agriculture; MQTT; sensors; Cloud networking.